TorakochirurgiaAutofluorescence bronchoscopy in diagnostics and treatment of the lung cancer - Donat, Piotr; Ramlau, Rodryg; Nowak, Elżbieta; Barinow-Wojewódzki, Aleksander (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Lung cancer is the most frequent malignant cancer in the world and it is characterized by the highest mortality rate. This type of cancer is the reason of about 20% of all deaths caused by cancerous diseases. On average, 28% of males and 10% of females die of lung cancer. The majority of ill people, who have undergone a diagnostic process, are considered to be at an advanced stage of this disease. Patients suffering from lung cancer have a relatively little chance of effective and permanent recovery. Prognosis of lung cancer remains disadvantageous. Early diagnosis has a decisive impact on the success in treatment. The risk of incidence is the highest among smokers, therefore, the role of primary prevention, i.e. breaking the habit, is crucial here. The cancer screening is oriented to detect earlier stages of advanced lung cancer. In the last couple of years, the modern diagnostic methods have been developed including autofluorescence bronchoscopy. The following review shows case studies related to fluorescence of cells, the effects of autofluorescence bronchoscopy as well as possibilities of its usage in bronchology.